Suggestopedia: A Method for Teaching and Learning in Informal Educational Settings - Novi Indriyani (Departement of Mathematics Education, 2024)
This paper aims to investigate the implementation of Suggestopedia by a teacher in an English institution, following Lozanov's four main stages of activities: presentation, concert, elaboration, and practice. The data were obtained through observation focusing on teacher activities during the implementation and observed effectiveness of the Suggestiopedia method in the language learning session. The positive outcomes of using Suggestopedia in language learning sessions suggest promising prospects for future applications in educational settings. It is essential to recognize the transformative impact it can have on language learning when implemented thoughtfully and inclusively. By addressing the diverse needs and preferences of language learners, and integrating a balanced approach that combines diverse learning modalities, meaningful language applications, and comprehensive language practice and assessment, educators can maximize the effectiveness of this approach.